Using large samples in econometrics - James G. MacKinnon (Queen's University, Department of Economics, 2021)
As I document using evidence from a journal data repository that I manage, the datasets used in empirical work are getting larger. When we use very large datasets, it can be dangerous to rely on standard methods for statistical inference. In addition, we need to worry about computational issues. We must be careful in our choice of statistical methods and the algorithms used to implement them.
Keywords: C10; C12; C13; C55; 330; datasets; clustered data; statistical computation; statistical inference; bootstrap